ТАСВИРИЙ САНЪАТ ДАРСЛАРИДА ШАРҚИЙ ОСИЁ РАНГТАСВИРИДАН ФОЙДАЛАНИШ - Абдирасилов, С.Ф. (SCIENCE and SOCIETY, 2022)
This article discusses the Chinese art of East Asia at the lessons of fine arts, and a practical demonstration of the methods of work in the form of painting for students of secondary schools. An orchid is presented as methodological materials for teachers of fine arts, the technology of work on creating a traditional image of bamboo.
Keywords: Chinese painting; calligraphy; hieroglyph; traditional images - bamboo; orchid; chrysanthemum; paint strokes; watercolor brush